A Physiologic Regulator of Collagen-Induced Platelet Aggregation: Inhibition by Clq - Csákó, György; Suba, Eva A (Thrombosis and Haemostasis, 1981)
Platelet aggregations were studied by a turbidimetric method in citrated human platelet-rich plasmas (PRP) in vitro. Human Clq inhibited the aggregations caused by collagens derived from different tissues and species. Clq was needed by weight in comparable quantities to collagen for neutralizing the aggregating effect. The dependence of the inhibitory reaction on the preincubation of platelets with Clq and the differences in the occurrence of aggregating substances in supernatants of PRP triggered with collagen in the presence or absence of Clq, confirmed that Clq exerts its effect by preventing fixation of collagen to platelets. In addition, the high specificity of the inhibitory action of Clq for collagen-induced platelet aggregation was demonstrated by results obtained for testing a variety of aggregating agents in combination with Clq and/or collagen.Since normal concentrations of Clq in the blood are in the range of inhibitory doses of Clq for collagen-induced platelet aggregations in vitro and upon activation of complement Clq is known to dissociate from Cl, it is proposed that Clq may participate in a highly specific manner in regulating platelet reactivity to collagen in vivo.
Keywords: Platelets; Subcomponent Clq; Collagen